ANALYSIS OF THE CONTRACT MECHANISM IN SHARIA VENTURE CAPITAL AND ITS RELEVANCE TO MSME FINANCING - Hendra, Joni; Syantana, Ade Vieea; Khairunnisa, Khairunnisa; Liani, Fenny; Almuttaqin, Femas; Algifari, Muhammad; Utomo, Budi (LPPM Univ. Ibn Khaldun Bogor, 2026)
Sharia Venture Capital is an alternative financing instrument that offers a partnership-based scheme oriented toward fairness and free from elements of usury. This study aims to analyze the contractual mechanisms used in Sharia venture capital and their relevance for financing Micro, Small, and Medium Enterprises (MSMEs). The research was conducted using a qualitative approach through a literature review that examines the concept of Sharia venture capital, contract structures, and the characteristics of MSME financing needs. The analysis shows that the most commonly used contracts in Sharia venture capital are musyarakah, mudharabah, and wakalah bil ujrah. Each contract has distinct characteristics that address the needs of partnership-based financing, risk-sharing, and business mentoring. The study finds that this financing model is highly relevant for MSMEs, particularly because it does not require collateral, emphasizes profit-sharing, and provides managerial support. However, its implementation still faces several challenges, such as low Islamic financial literacy and the limited number of Sharia venture capital institutions in Indonesia. This study is expected to serve as a foundation for developing a more inclusive and Sharia-compliant MSME financing model.